(untitled) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2022)
In 2021, Peru celebrated 200 years of independence, marking an important milestone in its history, which leads us to the following question: In these 200 years, how much progress has been made in business studies in Peru? We found bibliometric analysis to be the most appropriate method to answer this question. The software used to analyze the interrelationships between articles was Vosviewer, a software that allows the creation and visualization of bibliometric networks. Using the search terms "Peru" and "Business", we retrieved 908 articles from the Scopus Database.